Pengembangan Multimedia Pembelajaran Interaktif Pada Materi Pengenalan Bangun Datar Sederhana Menggunakan Metode Invariant Moment di Kelas I Semester II SD Negeri 1 Keramas - I Gusti Agung Wahyu Prayoga; I Made Gede Sunarya; I Gede Mahendra Darmawiguna (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2014)
This study aimed at 1) designing and implementing the interactive learning multimedia for introductions of 2-dimensional shapes using invariant moment method, and 2) describing students’ responses to the implementation of the interactive learning multimedia for introductions of 2-dimensional shapes using invariant moment method. This multimedia is a web-based multimedia.  The recognition process of 2-dimensional shape on this multimedia used invariant moment method. This study used the Dick and Carey development model which combined with the Waterfall Model. The subjects of this study were 20 students of I B SD Negeri 1 Keramas in academic year 2013/2014, an expert of content, an expert of learning media, and an expert of learning media design. The objects of this study were the interactive learning multimedia for introductions of 2-dimensional shapes using invariant moment method in mathematics, the result of the expert content test, the expert media test, the expert media design test, and students’ responses.  Guidelines for interviews and questionnaires are used to know the response of the subjects about this interactive learning multimedia and its effectiveness. Data were analyzed descriptively. The results showed 1) the menus on this multimedia have different function, 2) students' responses this multimedia  is in the positive category with an average score of 62,95.